PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS DAN UKURAN PERUSAHAN TERHADAP AGRESIVITAS PAJAK - Nurfidinia Karin Putri; Erlina Diamastuti (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
The purpose of this study was to test the influence of Corporate SocialResponsibility Disclosure, profitability, and company size on tax aggressiveness ofcompanies listed on the SRI-KEHATI Index 2015-2018. This study uses aquantitative approach in looking at the problems to be tested. Data collection usessecondary data in the form of annual financial reports and corporate sustainabilityreports listed in the SRI-KEHATI index. The population in this study werecompanies listed on the SRI-KEHATI index 2015-2018, while the sample of thisstudy was selected using the purposive sampling method. The number of sampledata that met the criteria was 13 companies. The data analysis technique in thisstudy used multiple linear regression analysis and the data were processed usingSPSS 25. The results of this study indicate that Corporate Social Responsibility(CSR) disclosure has no effect on tax aggressiveness, while profitability and firmsize have an effect on tax aggressiveness.